2017
DOI: 10.3847/1538-4365/229/1/11
|View full text |Cite
|
Sign up to set email alerts
|

Slender Ca ii H Fibrils Mapping Magnetic Fields in the Low Solar Chromosphere

Abstract: A dense forest of slender bright fibrils near a small solar active region is seen in high-quality narrowband Ca II H images from the SuFI instrument onboard the SUNRISE balloon-borne solar observatory. The orientation of these slender Ca II H fibrils (SCF) overlaps with the magnetic field configuration in the low solar chromosphere derived by magnetostatic extrapolation of the photospheric field observed with SUNRISE/IMaX and SDO/HMI. In addition, many observed SCFs are qualitatively aligned with small-scale l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 76 publications
4
43
0
1
Order By: Relevance
“…Our observations cannot, however, clarify whether this energy is dissipated in the sampled atmospheric layers. The apparently almost horizontalorientationof the majority of the SCFs studied here, many of which connect back to the solar surface as low-lying loops (see Jafarzadeh et al 2017a), suggest that the waves propagating along them may not reach the upper atmosphere. Rather, they play a role in heating their local surroundings, if they release their energy at these layers.…”
Section: The Structures Listed Inmentioning
confidence: 88%
See 2 more Smart Citations
“…Our observations cannot, however, clarify whether this energy is dissipated in the sampled atmospheric layers. The apparently almost horizontalorientationof the majority of the SCFs studied here, many of which connect back to the solar surface as low-lying loops (see Jafarzadeh et al 2017a), suggest that the waves propagating along them may not reach the upper atmosphere. Rather, they play a role in heating their local surroundings, if they release their energy at these layers.…”
Section: The Structures Listed Inmentioning
confidence: 88%
“…These events may, however, share some apparent and/or physical characteristics (e.g., both types of underlying fibrils are observed as short-lived, dynamic, thin and bright elongated features in the Ca II H passband). Jafarzadeh et al (2017a)showedthat the SUNRISE/SuFI SCFs map the magnetic fields in the low solar chromosphere.…”
Section: The Structures Listed Inmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures, seen in radiation, are thought to follow magnetic field lines (e.g., Jafarzadeh et al 2017b) anchored in photospheric magnetic flux concentrations, or in the weaker internetwork elements (Wiegelmann et al 2010). Except for regions with large magnetic flux concentrations, such as sunspots or large pores, these structures play an important role in transporting the energy from the solar surface to the chromosphere and to the corona, either as a channel for the propagation of waves (e.g., van Ballegooijen et al 2011), or as the location for small-scale reconnection events (Gold 1964;Parker 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Their range of periods overlaps with those of the MBPs we observe in this study. The slender CaIIH fibrils have been shown to outline the nearly horizontal magnetic field lines in the low solar chromosphere, slightly higher than the heights, where our CaIIH MBPs were sampled (Jafarzadeh et al 2017a). Since such fibrils have footpoints in photospheric magnetic features, such as MBPs, we speculate that waves of the type observed here partly continue into the chromosphere and may become visible as oscillations of fibrils.…”
Section: Comparisons and Discussionmentioning
confidence: 99%